Analysis of Students' Learning Difficulties in Subtracting Whole Numbers in Grade 3 Elementary School - Manovtri, Reni; Hayati, Rahmatul (Pusdikra-Publishing.com, 2024)
This research aims to analyze the learning difficulties of grade 3 elementary school students in understanding the material for subtracting whole numbers. Difficulties experienced by students include conceptual, procedural, calculation errors, and difficulties in solving word problems. Factors causing these difficulties include internal aspects, such as low understanding of mathematical concepts, lack of motivation, and concentration problems, as well as external factors, such as less varied learning methods, minimal use of interactive media, and lack of learning environment support. The results of the analysis show the importance of implementing innovative learning strategies, such as contextual approaches, using teaching aids and interactive technology, as well as providing individual guidance and collaboration with parents. With these efforts, it is hoped that students can understand the concept of subtracting whole numbers better and improve their overall mathematical abilities.